PENGARUH KEPEMIMPINAN TERHADAP SEMANGAT KERJA PEGAWAI DI SEKRETARIAT DAERAH KOTA SOLOK - GUSRA NELMI YOLLA (Jurnal Bahana Manajemen Pendidikan, 2016)
This research decribes the relationship between a leadership and the employee moralein the secretariat solok city area. The population  in this research were all employees of the secretariat solok city area, they were 150 employees. The number of samples were 67 people, taken by using proportional startified random sampling technique. The instrument use in this research is questionnaire in likert scale model that had been tested for validity and reability. Based on the research, leadership in the good category 82,67% and the employee morale in the enough category in the amount of 79,7 %. There is a significant influence between the leadership of the employee morale in the secretariat solok city area great influence  is r2= 0,369 (36,9%).